The better regulation agenda: a 'new deal' in the building of Europe? - Van den Abeele, Eric (Brussels, 2009)
"Scrutiny of the Better Regulation agenda reveals the European Commission’s use of doublespeak. Feigning a concern for modernisation, simplification and improvement of the quality of Community regulation, the Commission has embarked, with the help of the Council and the tacit approval of the European Parliament, on an insidious enterprise to deregulate the Community acquis. ‘Business competitiveness must be saved’ is the endlessly repeated refrain employed to curb the Commission’s right of legislative initiative, limit the co-legislators’ right of amendment and reduce the administrative and regulatory burden entailed by Community provisions. Bureaucratisation of the process and the sudden appearance of new actors (private consultants and interest groups) must alert us to the true aims of the Better Regulation agenda."